Remembering Sugihara, Re-framing Japan in Europe: Holocaust Era Altruism and the Politics of Cultural Memory - Law, Jane Marie Marie (Acta Orientalia Vilnensia, 2006)
Cornell UniversityThis paper is a comparison of two museums dedicated to the Japanese diplomat to Lithuania during World War II, Sugihara Chiune. Credited with having written over 6,000 visas to save the lives of Jews fleeing German occupied Poland into Lithuania, Sugihara is regarded in Europe, in Japan, and within the Jewish community as a whole as an altruistic person. This study is not an inquiry into the merits of Sugihara’s action, but rather astudy of how the process of memorializing, narrativizing and celebrating the life of Sugihara in two vastly different museums is part of a larger project of selective cultural memory on the part of various Japanese organizations and institutions. This paper situates the themes of altruism and heroism in the larger process of cultural memory, to see how such themes operate to advance other projects of collective memory. The case of Sugihara is fascinating precisely because the vastly differing processes of cultural memory of the Holocaust―in Lithuania, in Japan, and in a wider post-World War II, post Holocaust Jewish Diaspora each have different ways of constructing, disseminating and consuming narratives of altruism. This paper is based on fieldwork in Kaunas and Vilnius, Lithuania, in 2003, 2004 and again in 2005 and in Japan in 2005.